COMMUNITY EMPOWERMENT THROUGH THE MOTORCYCLE MECHANIC TRAINING PROGRAM AT THE WORK SERVICE CENTRE - Sabiruddin, Sabiruddin; Basra, Sri Meiweni; Yenis, Muhammad; Japeri, Japeri (Universitas Islam Negeri Raden Intan Lampung, 2023)
Lack of education, low skill levels, the more competitive nature of the job market, laziness, a lack of discipline, a lack of drive to live, and a failure to uphold religious principles are all contributing factors to unemployment issues. The aforementioned factors have led the Pariaman City/Padang Pariaman Regency government to prioritize the skills of its human resources through the Motorcycle Mechanic Training program offered by the Pariaman City/Padang Pariaman Regency Job Training Center. In this study, various training obstacles such as individuals who attend training against their will, without knowing the direction and objectives to be met, without commitment, who merely show up to fill in time instead of finding another job, and so on were found at the Job Training Center of Pariaman City. To overcome the problems and obstacles that occur, the efforts made by the Job Training Center of Pariaman are to provide direction, motivation, and intensive assistance according to the needs of participants by the instructor. In addition, it also holds mental, physical, and disciplinary honing activities, provides external assistance by psychologists, and provides training and seminars related to job access in collaboration with private companies invited by the Job Training Center of Pariaman City, Padang Pariaman Regency. The training held can assist local governments in tackling unemployment problems in Padang Pariaman Regency.